Bonus payments for electricity production from renewable energy sources and the impact on the market participants' capacity choice - Kai Flinkerbusch (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2010)
Promoting the use of renewable energy sources is a central goal of most industrialized countries. Up to today, fixed feed in tariffs are a commonly used support scheme. However, these have major disadvantages concerning market integration. Thus, more market-conforming solutions come into focus. One of these are bonus payments. Their fundamental characteristic is an augmented market price for the production of electricity from renewable energy sources. This paper takes a closer look at the mechanics of bonus payments in an environment of market power and negative externalities connected to conventional electricity supply. We analyze the market participants' behavior in a long-term context: Suppliers react to an augmented price by adapting their level of capacity. It is an important question whether a social optimum can be reached by means of bonus payments or whether welfare losses occur. We use a two-stage model. In the first stage the public sector implements the bonus payment. In the second stage, the suppliers engage in Cournot competition, choosing their profit maximizing level of capacity. We find that in this setting, bonus payments can strongly increase overall welfare. However, they do not prove to be superior instruments for the promotion of renewable energy as they, like fixed feed in tariffs have major disadvantages compared to more market conforming instruments.
Keywords: 330; renewable energy; bonus payments; capacity investment